Means and methods of harmonic physical students' development in the process of independent studies of physical exercises - Sychov S.O (Kharkov National Pedagogical University, 2010)
Organization of process of independent employments is considered by physical exercises. Facilities and methods of harmonic physical development of students open up. 56 students (an experimental group is 26 students; control are 30 students) of I-IV of courses took part in research. Developed recommendation on the use of physical exercises for perfection of independent work on physical education. Directions of self-control are rotined after physical preparedness, health level, ability to adhere to principles of dosage of loadings and optimum pulse modes.